Evaluation of Modern Architecture and Urbanism Development in Qajar Houses Architecture (Case Study:Kermanshah City in the Western Region of Iran) - Pegah Chaleshgare; Mojgan Khakpoor; Ali Asgharzadeh (جغرافیا و آمایش شهری منطقه‌ای, 2021)
Architectural developments and urban spaces of kermanshah during qajar period coincided with the emergence of the process of development and physical growth of iranian cities, due to the arrival of qajar princes in kermanshah and the effects of the communication situation of this city. Thus, the necessary ground was created for the formation and development of urban spaces and architecture, change of social relations, separation of social strata and the emergence of new needs. In this research, the formation of qajar houses architecture in the western region of iran and especially kermanshah city and the relationship between architectural development patterns and modern urbanism with qajar house architecture have been discussed as the main questions of the research.this research is a historical, interpretive method based on three stages of "evaluation of the process of architectural development and components of the impact of western urban planning in qajar houses", "study of landmark houses based on theoretical foundations and how western architecture and modern urban space affect the architecture of the qajar period" and "how the formation and transformation influenced by western architecture and modern urban space and its reflection on the body of architecture and urban planning in the houses of kermanshah in the western region of iran" was done.the analysis of the subject in this paper was possible based on the collection of information in the form of documents, libraries and field studies to examine the scope of study. The findings show that the qajar government has provided the grounds for changes and modelling of western civilization in the traditional space of iranian society and in this period,buildings with a style combined with elements and decorations influenced by western architecture and urban development patterns have emerged in iranian architecture.the evaluation process in this study according to the defined characteristics, indicates that the degree of impact and modeling includes the period of continuation of iranian architectural traditions, the period of combining traditional iranian architecture with western architecture and the period of replacing western architecture with traditional iranian architecture.the evolution and physical changes of the architecture of the qajar houses of kermanshah have been made possible based on the dependence on social, economic, political and cultural changes in the formation and development structure of the qajar city of kermanshah.